2022
DOI: 10.1186/s12967-022-03398-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ISG15 and ZFP36 as novel hypoxia- and immune-related gene signatures contributing to a new perspective for the treatment of prostate cancer by bioinformatics and experimental verification

Abstract: Background Prostatic cancer (PCa) is one of the most common malignant tumors in men worldwide. Emerging evidence indicates significance of hypoxia and immunity in PCa invasion and metastasis. This study aimed to develop a hypoxia- and immune-related gene risk signature and explore the molecular mechanisms to formulate a better prognostic tool for PCa patients. Methods The hypoxia and immune scores of all PCa patients in The Cancer Genome Atlas (TCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Several studies have shown that patients with higher immune scores and lower stromal scores have a better prognosis ( 49 , 50 ). However, the low-CRIRS group with a better prognosis had higher stromal scores and lower immune scores, and no significant differences in immune microenvironment scores were observed between the low and high CRIRS groups in our study ( Figures 9A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that patients with higher immune scores and lower stromal scores have a better prognosis ( 49 , 50 ). However, the low-CRIRS group with a better prognosis had higher stromal scores and lower immune scores, and no significant differences in immune microenvironment scores were observed between the low and high CRIRS groups in our study ( Figures 9A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent meta-analysis study identified miR-21 as one of several miRNAs that could predict responses to androgen-deprivation therapy [95]. Elsewhere, various research groups have developed hypoxic signature panels of gene markers to predict prostate cancer prognoses and treatment outcomes, although notably these did not include microRNAs [96][97][98][99]. Our research suggests that hypoxia-induced miRNAs should really be included in such panels, especially if blood-based markers are preferred.…”
Section: Discussionmentioning
confidence: 97%
“…ISG15 was the first ubiquitin-like protein (Ubl) to be identified and acts not only in the unconjugated/conjugated form inside the cell, but also in the free form outside the cell [ 10 , 21 ]. ISG15 and the enzymes that catalyze ISGylation and de-ISGylation are dysregulated in many types of cancer, including breast, pancreatic, and prostate cancers [ 14 , 22 24 ]. However, it remains uncertain whether ISG15 and ISGylation play a pro-tumor or anti-tumor role in cancer.…”
Section: Discussionmentioning
confidence: 99%